Epidemiological aspects of HIV infection and AIDS among indigenous populations - Samara Vilas-Bôas Graeff; Renata Palópoli Pícolli; Rui Arantes; Vivianne de Oliveira Landgraf de Castro; Rivaldo Venâncio da Cunha
ABSTRACT OBJECTIVE To describe the epidemiological aspects of HIV infection and AIDS among indigenous peoples of the state of Mato Grosso do Sul, Brazil. METHODS This is a descriptive epidemiological study on the occurrence and distribution of HIV infection and AIDS in the indigenous population assisted by the Distrito Sanitário Especial Indígena (Indigenous Special Health District) Mato Grosso do Sul between 2001 and 2014, based on three secondary databases. Annual rates of HIV and AIDS detection and prevalence were calculated, considering case distribution according to village, Health Base Pole and sociodemographic variables. Accumulated rates of detection, mortality and case fatality were calculated by ethnic group and for the Health Base Pole with the highest number of cases. RESULTS The HIV detection rate fluctuated between 0.0 and 18.0/100 thousand people in the study period. For AIDS, there was no notification before 2007, but in 2012 its rate reached 16.6/100 thousand. HIV prevalence grew between 2001 and 2011, and it continuously grew for AIDS starting from 2007. The highest HIV detection rates occurred among Guarani peoples (167.1/100 thousand) and for AIDS, among the Kaiowá peoples (79.3/100 thousand); mortality and fatality rates were higher among the Kaiowá. Regarding the Dourados Health Base Pole, the AIDS detection rate increased, and the mortality and fatality rates decreased. CONCLUSIONS HIV infection and AIDS have been increasing among indigenous peoples, with distribution of the disease mainly in the Health Base Poles of the southern region of the state, where greater economic and social vulnerability are also observed. The endemic character of HIV and AIDS can become epidemic in some years given the existence of cases in other villages in the state. Its occurrence among the Guarani and Kaiowá populations indicates the need for expanded diagnosis, access to treatment and prevention measures.